Interactions of polysaccharide stabilising agents with early cement hydration without and in the presence of superplasticizers. (15th May 2017) - Schmidt, Wolfram; Brouwers, Henricus Jozef Hubertus; Kühne, Hans-Carsten; Meng, Birgit
Graphical abstract: Highlights: The effect of polysaccharide stabilising agents on rheology and setting was studied. Diutan gum affects yield stress in the liquid efficiently, while starch requires particles. In the presence of superplasticizers, starch and diutan gum have similar effects. Stabilising agents can reduce retarding effects of superplasticizer. Abstract: Polysaccharides are incorporated into cement based systems in order to modify the rheological properties. Typically, cellulose ethers, sphingan gums, guar gum or starch ethers are applied. Depending upon their chemistry, molecular architecture, and adsorption tendency, polysaccharides interact differently with the entire cementitious system. Some stabilising agents like diutan gum mainly affect the cementitious paste; other stabilising agents like starch tend to interact with the sand fraction and even with the coarse aggregates. Cellulose and guar gum shows more diverse performances. Typically stabilising admixtures like polysaccharides are used, when sophisticated rheological properties are adjusted. Therefore, polysaccharides are often used in combination with superplasticisers, which are added to reduce the yield stress of concrete. This can cause interactions, particularly when the stabilising agent shows a strong tendency to adsorb on particle surfaces. Adsorptive stabilising agents may reduce the amount of adsorbed superplasticisers, thus affecting both viscosity and yield stress, while non-adsorptive stabilising agents mainly affect the plastic viscosity independently of the superplasticiser. Due to the strong influence of superplasticisers on the yield stress, influences of the stabilising agent on the yield stress retreat into the background, so that their major effect is an increase of the plastic viscosity. The paper provides a comprehensive overview of how different polysaccharide superplasticisers affect cementitious flowable systems and points out the challenges of the combined use of polysaccharides and superplasticisers. Based on rheometric experiments and observations of the hydration process, time dependent effects on the workability as well as of the hydration of cement are presented and discussed.